What drives firm profitability? A comparison of the US and EU food processing industry - Adelina Gschwandtner; Stefan Hirsch (University of Kent, School of Economics, 2016)
This article analyzes persistence and the drivers of profitability in US and EU food processing using GMM estimations. Due to different firm size structures first comparable samples of US and EU food processors are derived using Propensity Score Matching. The GMM results indicate that profit persistence in food processing is lower than in other manufacturing sectors. Firm-specific drivers of profitability are size, growth and financial risk. Regarding industry characteristics the growth rate significantly influences profitability. The findings provide insights for the management of food processing firms as well as for policy decisions aiming to counter power imbalances in the food sector.
Keywords: L12; L66; M21; 330; Firm profit; persistence; food industry; GMM panel estimation; propensity score matching